A Dispersion Index for the Analysis of the Distribution of Activities in the Tunisian Coastal City of Nabeul - Narjiss Bakhtyari; Asma Rejeb Bouzgarrou; Christophe Claramunt; Hichem Rejeb (Geomatics, 2022)
This research investigates the duality of the spatial organization and urban activities generated by the coastalization processes of the city of Nabeul. The first part of the study analyzes the city’s fragmentations of the urban landscape using a novel generic index of directional dispersion and a set of space syntax metrics. These structural and functional properties are studied by the concentration and/or dispersion of urban functions of the evolution and development patterns. Among the emerging features, we observe a dispersion of urban activities beyond a central radius all along the western periphery of the city, confirming the phenomenon of urban sprawl that many Tunisian cities are experiencing. These spaces generate urban fragmentations of “new polarity zones” under the influence of the coastline attraction. Finally, this study introduces a novel approach for identifying urban structural polarity and activities, as well as new perspectives for coastal land management and planning.